Administrative Law without Borders - Jakub Handrlica (Bratislava Law Review, 2023)
An international conference, entitled “Administrative Law without Borders” was organised by the Faculty of Law, University of Košice in the municipality Veľká Třňa, which is situated in the very heart of the Slovak area of the Tokaj wine region. The conference was organised under the research project “Extraterritorial effects of foreign administrative decisions in the European Union”, which has been supported by the Scientific Agency VEGA. The Košice-based research team, under the leadership of Associate Professor Radomír Jakab, has been dealing with various problems arising from mutual recognition of foreign administrative decisions for several years, and the conference, as organised on 19th and 20th October 2023 in the Tokaj Wine Region, represents one of the major academic meetings organised under the umbrella of this academic endeavour.